KERAGAMAN TUMBUHAN INVASIF DI HUTAN PENELITIAN DRAMAGA BOGOR - Purwohadi Purbo Priyono; . Ismanto; Adi Susilo (Universitas Pakuan, 2021)
Invasive Plant is species that dominate an area or places, both are native species and non-native species. Invasive Plants is one of the crucial problems in ecosystem management because it is a major component of global environmental change, threats to biodiversity and local species, as well as, causes of changes in nutrient cycles, fire cycles, hydrological cycles, and energy balance. The purpose of this study is to prove that plants far from the road are more commonly invaded by invasive species and that physical and biological factors affect the growth of invasive species. The research was conducted at the Dramaga Research Forest, Bogor from June 2020 to August 2020. This study used a vegetation analysis method, which is using nesting plots that have a size of 2 x 2 m for seedlings, 5 x 5 m for saplings, 10 x 10 m for poles, and 20 x 20 m for trees. Plots were made in two locations, close to the road and far from the road. The location close to the road was 5 - 10 meters, and far from the road was 70 - 80 meters The total plots made in this study were 16 plots in each size. The results showed that the highest diversity was found at the level of seedlings, namely medium status (2.00-3.00) according to the Shannon-Wiener index. The results showed that the statistical analysis of the diversity of weeds in the Dramaga Research Forest were not significantly different, between plants close to the road and plants far from the road. This is causing by physical factors that are not significantly different based on statistical tests. The growth of invasive plant species is influenced by several factors, such as light intensity, temperature, humidity, and soil pH.Â Keywords: Dramaga Research Forest Bogor, Invasive species, Vegetation analysis